Relationship between velopharyngeal closure, hypernasality, nasal air emission and nasal rustle in subjects with repaired cleft palate - Scarmagnani, Rafaeli Higa (2015)
To investigate the correlation among velopharyngeal closure, hypernasality, audible nasal air emission (NAE) and nasal rustle (NR), in individuals with repaired cleft palate. METHODS: One hundred patients with repaired cleft palate and lip, submitted to pressure-flow study for measurement of velopharyngeal orifice area (velopharyngeal area) and speech sample recordings. Velopharyngeal area was estimated during the production of the sound /p/ inserted in a sentence, and the velopharyngeal closure was classified as adequate, borderline or inadequate. Hypernasality was rated using a 4-point scale, NAE and NR were rated as absent or present, by three speech language pathologists, using recorded speech samples. Inter and intra-judge agreements were established. Statistical analysis was performed using the Spearman correlation coefficient considering p<0.05. An ordinal logistic regression model was developed to investigate whether the characteristics of speech can predict velopharyngeal closure. For this, the speech samples included in this analysis were those that obtained 100% agreement among raters as to the degree of hypernasality (43 out of 100). RESULTS: Significant correlation was found between hypernasality and velopharyngeal area; audible NAE and velopharyngeal area. A negative correlation was observed between the NR and velopharyngeal area. The regression analysis showed that the perceptual speech characteristics contributed significantly to predict the velopharyngeal closure. CONCLUSION: There is significant correlation between velopharyngeal closure and hypernasality, NAE and NR. It suggests that the perceptual speech characteristics can predict velopharyngeal closure, favoring the diagnosis and the definition of treatment conduct of velopharyngeal dysfunction.